Role of the nurse working in the family health strategy in the prevention of prostate cancer (Research, Society and Development, 2022)
The World Health Organization considers that prostate cancer is the second in incidence, and the sixth most frequent cause of death in the world's male population, and has been accompanied by several health care services across the globe. In Brazil, among the public services offered by the Unified Health System for health promotion and disease prevention, there is the Family Health Strategy, which is a multidisciplinary team composed of several health professionals, including nurses. Given this context, the general objective of this study was to discuss and analyze the role of the nursing professional participating in the Family Program strategy, as a mediator in the awareness and prevention of Prostate Cancer. The methodological procedures involved bibliographic research with literature review through secondary sources and a descriptive qualitative approach. The results showed that the role of nurses in the Family Health Strategy has become essential as an active agent in the health of the population, and in preventive care actions and guidelines in the early identification of prostate cancer, as well as in the direction for specific treatment. , in care and assistance services. Although there is a lower adhesion of the male population in the search for health services, especially in preventive matters, the nurse plays the role of mediator in this action, which makes the approach, reception and creation of a bond a challenge to be overcome by the team. of nurses from the Family Health Strategy, in the prevention, guidance and assistance on prostate cancer.